2021
DOI: 10.1186/s12906-021-03439-3
|View full text |Cite
|
Sign up to set email alerts
|

Herbal medicines use and associated factors among pregnant women in Debre Tabor town, north West Ethiopia: a mixed method approach

Abstract: Background Use of herbal medicines during pregnancy has been increase in many developing and developed countries. In spite of the studies done on herbal medicine, no study has addressed use of herbal medicine among pregnant women in Debre Tabor Town. Hence, the major aim of this study was to assess the prevalence of herbal medicine use and associated factors. Methods A community based explanatory sequential mixed methods was employed. The quantitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 17 publications
1
9
0
1
Order By: Relevance
“…Nevertheless, consistent with previous ndings, the primary reason for non-disclosure of T/CM use was the lack of inquiry from obstetric care providers, while the majority of T/CM users were willing to disclose their use if the conversation was initiated by their providers 19,[53][54][55] . These ndings emphasize the importance of healthcare providers' role in promoting effective communication about various healthcare approaches, including T/CM, to ensure patient safety and health.…”
Section: Discussionsupporting
confidence: 80%
“…Nevertheless, consistent with previous ndings, the primary reason for non-disclosure of T/CM use was the lack of inquiry from obstetric care providers, while the majority of T/CM users were willing to disclose their use if the conversation was initiated by their providers 19,[53][54][55] . These ndings emphasize the importance of healthcare providers' role in promoting effective communication about various healthcare approaches, including T/CM, to ensure patient safety and health.…”
Section: Discussionsupporting
confidence: 80%
“…Among 111 studies, 102 studies were cross-sectional in design 27 61–161. Three studies used mixed-method approaches,162–164 and six studies had non-cross-sectional designs (ie, longitudinal and case–control),165–170 but reported cross-sectional data on HM use during pregnancy (online supplemental appendix 6). Regarding the geographical distribution of included studies, a majority of them were conducted in Africa 66 69 77 81 82 89 91 95 98 100 101 105 106 115 116 119 121–123 129 132–135 137–140 143 144 146 150 153 156 158–164.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies used mixed-method approaches,162–164 and six studies had non-cross-sectional designs (ie, longitudinal and case–control),165–170 but reported cross-sectional data on HM use during pregnancy (online supplemental appendix 6). Regarding the geographical distribution of included studies, a majority of them were conducted in Africa 66 69 77 81 82 89 91 95 98 100 101 105 106 115 116 119 121–123 129 132–135 137–140 143 144 146 150 153 156 158–164. Lastly, 21 out of 111 studies presented findings related to pregnant women’s disclosure of HM use to their healthcare providers 27 70 73 83 85 86 91 109 110 115 117 122 125 126 129 133 142 149 155 160 164…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pregnant women usually do not consult the use of herbs with a doctor or pharmacist [ 6 ]. Data demonstrated that almost 95% of Ethiopian pregnant women did not consult the usage of herbal medicines with the doctor or nurse [ 7 ]. In Norway, only less than 12% of pregnant women were recommended to use herbs by healthcare personnel [ 8 ].…”
Section: Introductionmentioning
confidence: 99%